PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN METODE CLASS CONCERN DENGAN PEMBELAJARAN METODE KONVENSIONAL PADA MATA PELAJARAN AKUNTANSI KELAS X SMK KARTIKA 1-2 PADANG - Yelliza, Yelliza; Arza, SE,M.Sc,Akt, Fefri Indra; Dahen, Lovelly Dwinda (Pendidikan Ekonomi, 2014)
Â This research was motivated by the low learning outcomes of accounting students Grades 1-2 Kartika X SMK Padang Academic Year 2013/2014 . This is caused by the lack of activity of students in the learning process .This study aims to determine the differences in accounting student learning outcomes using Class Concern with conventional learning method on Class X SMK Kartika 1-2 Padang . This research is an experimental study. The study population is a Class X student of SMK Padang 1-2 Kartika Academic Year 2013/2014 . Samples were taken with a random sampling technique , was selected as the class Xai Xai experimental class and the class as a control class .The instrument used was a test of student learning outcomes . Data analysis techniques to test the hypothesis is the t-test. Based on the analysis of data obtained an average value of 78.64 experimental class and control class average of 69.78 . From the analysis of the data found the value of t = 2.55 is greater than the table = 2.000 which means that the hypothesis is accepted at significance level Î± = 0.05 . This suggests that there are significant differences between the results of student learning method using Class Concern with conventional learning methods . This means that the accounting student learning outcomes using Class Concern better method of accounting student learning outcomes learning process using conventional teaching methods on Class X SMK Padang Kartika 1-2. .